Intratracheal instillation for the testing of pulmonary toxicity in mice—Effects of instillation devices and feed type on inflammation - Niels Hadrup; Michael Guldbrandsen; Eva Terrida; Katja M. S. Bendtsen; Karin S. Hougaard; Nicklas R. Jacobsen; Ulla Vogel (Animal Models and Experimental Medicine, 2025)
Abstract Background Inhalation exposure is the gold standard when assessing pulmonary toxicity. However, it typically requires substantial amounts of test material. Intratracheal instillation is an alternative administration technique, where the test substance is suspended in a liquid vehicle and deposited into the lung via the trachea. Instillation requires minimal test material, delivers an exact dose deep into the lung, and is less labor‐intensive than inhalation exposures. However, one shortcoming is that the procedure may induce short‐term inflammation. To minimize this, we tested different modifications of the technique to identify the potential for refinement. Methods First, we tested whether previous findings of increased inflammation could be confirmed. Next, we tested whether instillation with a disposable 1 mL syringe with ball‐tipped steel‐needle (Disposable‐syringe/steel‐needle) induced less inflammation than the use of our standard set‐up, a 250 μL reusable glass syringe with a disposable plastic catheter (Glass‐syringe/plastic‐catheter). Finally, we tested if access to pelleted and liquid feed prior to instillation affected inflammation. We evaluated inflammation by neutrophil numbers in bronchoalveolar fluid 24 h post‐exposure. Results Vehicle‐instilled mice showed a small increase in neutrophil numbers compared to untreated mice. Neutrophil numbers were slightly elevated in the groups instilled with Disposable‐syringe/steel‐needle; an interaction with feed type indicated that the increase in neutrophils was more pronounced in combination with feed pellets compared to liquid feed. We found no difference between the feed types when using the Glass‐syringe/plastic‐catheter combination. Conclusion The Glass‐syringe/plastic‐catheter combination induced the least exposure‐related inflammation, confirming this as a preferred instillation procedure.